Pengaruh Keadilan Distributif dan Keadilan Prosedural terhadap Kecurangan Akuntansi dengan Pertimbangan Etis sebagai Variabel Moderasi - Ikbal Ikbal; Syamsuri Rahim (Universitas Negeri Malang, 2019)
Abstract: This study aimed to determine the effect of distributive justice on accounting fraud, to determine the effect of procedural justice on accounting fraud, to determine the effect of moderat ethical considerations the effect of distributive justice on accounting fraud, to determine the effect of moderat ethical considerations the effec of procedural justice on accounting fraud. The data used is primary data. The data collection in this study used questionnaires distributed to 30 apparatus at SKPD Maros Regency. The data analysis by used the path analysis by the help of SPSS version 23.00. The results showed that the distributive justice has a positive and significant effect on accounting fraud at SKPD Maros Regency; the procedural justice has a negative and significant effect on accounting fraud in SKPD Maros Regency, the distributive justice does not affect on the tendency of accounting fraud moderated by ethical considerations at SKPD Maros Regency, the procedural justice affect on the tendency of accounting fraud moderated by ethical considerations in the Maros District SKPD.Abstrak: Penelitian ini bertujuan untuk menentukan dampak keadilan distributif dan keadilan prosedural pada kecurangan akuntansi. Selain itu, pertimbangan etis juga diuji sebagai variabel moderasi pada kedua hubungan tersebut. Data penelitian dihimpun dengan cara menyebarkan kuesioner kepada 30 aparat di SKPD Kabupaten Maros, dan diolah menggunakan analisis jalur dengan bantuan SPSS versi 23. Hasil penelitian menunjukkan bahwa keadilan distributif memiliki pengaruh positif-signifikan pada kecurangan akuntansi, dan keadilan procedural memiliki pengaruh negative-signifikan pada kecurangan akuntansi di SKPD Kabupaten Maros. Penelitian ini juga menemukan tidak adanya pengaruh pada tendensi kecurangan akuntansi yang dimoderasi oleh pertimbangan etis. Di sisi lain, keadilan procedural terbukti mempengaruhi kecurangan akuntansi saat dimoderasi oleh pertimbangan etis di wilayah SKPD Kabupaten Maros.